(untitled) (International Seven Journal of Multidisciplinary, 2024)
Introduction: The aging of the global population poses important medical and socio-economic challenges, and preserving this process is important for a healthier life for people who reach old age. With the impact of ageing on the elderly, it is possible to perceive some biological, physical, psychological and social changes, which can trigger various problems such as falls, chronic non-communicable diseases (CNCDs), nutritional changes and functional disabilities. Evidence shows an increase in the practice of physical exercise by the elderly, who are increasingly seeking a healthier and more active life. Aim: This study aimed to identify the anthropometric profile, self-perception of health and types of physical exercise practiced by elderly people in gyms in Rio Branco Acre. Results: The sample consisted of 83 elderly people, 74.70% were female and 25.30% were male, the average age in years was 67.20 ± (6.12), the average body weight was 69.50 ± (11.99) kg, the average height was 1.60 ± (0.09) cm and the body mass index - BMI was 27.00 ± (4.44). The prevalence of individuals with normal weight was 47.00% and overweight was 27.70%. The prevalence of health status was 48.20% for good health and 30.10% for regular health, while the prevalence of medication use was 88.00% and the prevalence of medical recommendations for physical exercise was 53.00%. The prevalence of the main types of exercise reported by the interviewees was bodybuilding (33.70%) and aqua aerobics (19.30%). The prevalence of time spent exercising (30 to 60 minutes) was 69.90%, and the weekly frequency of physical exercise (3 and 5 times a week) was 34.90 and 42.20% respectively. Conclusion: This study concludes that almost half of the interviewees are classified as normal weight, but almost all of the other half of the group are overweight or obese. With regard to general health, it was found that almost 88% of those interviewed were using some kind of medication, i.e. they already had some kind of illness, medical recommendations for physical exercise were decisive for more than half of the participants and the main types of exercise practiced were weight training and aqua aerobics.